2020
DOI: 10.3389/fmicb.2020.01711
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Cryphonectria parasitica Infected With Cryphonectria hypovirus 1 (CHV1) Reveals Distinct Genes Related to Fungal Metabolites, Virulence, Antiviral RNA-Silencing, and Their Regulation

Abstract: Comprehensive transcriptome analysis was conducted to elucidate the molecular basis of the interaction between chestnut blight fungus, Cryphonectria parasitica, and single-stranded RNA (ssRNA) mycovirus Cryphonectria hypovirus 1 (CHV1), using RNAsequencing (RNA-seq). A total of 1,023 differentially expressed genes (DEGs) were affected by CHV1 infection, of which 753 DEGs were upregulated and 270 DEGs were downregulated. Significant correlations in qRT-PCR analysis of 20 randomly selected DEGs and agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The virus significantly reduces virulence, growth and sporulation of the infected fungal strain, subsequently leading to recovery of infected chestnut trees (Anagnostakis, 1982; Brusini et al, 2017; Rigling & Prospero, 2018). On a molecular level, CHV1 has been found to significantly alter expression of genes in C. parasitica associated with virulence, primary and secondary metabolism, as well as carbohydrate metabolization (Chun et al, 2020). The virus has been used over decades as a naturally occurring or artificially released biocontrol agent against chestnut blight in Europe (e.g., Diamandis et al, 2014; Heiniger & Rigling, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The virus significantly reduces virulence, growth and sporulation of the infected fungal strain, subsequently leading to recovery of infected chestnut trees (Anagnostakis, 1982; Brusini et al, 2017; Rigling & Prospero, 2018). On a molecular level, CHV1 has been found to significantly alter expression of genes in C. parasitica associated with virulence, primary and secondary metabolism, as well as carbohydrate metabolization (Chun et al, 2020). The virus has been used over decades as a naturally occurring or artificially released biocontrol agent against chestnut blight in Europe (e.g., Diamandis et al, 2014; Heiniger & Rigling, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An example of how mycoviruses can impact on fungal metabolisms is well-represented by the interaction between the model host Cryphonectria parasitica (the causal agent of chestnut canker) and its virus Cryphonectria hypovirus 1. In more detail, it was demonstrated that the mycovirus infection produce a wide metabolic reprogramming of its host, modifying the whole primary and secondary metabolisms [58,64]. The same results were also achieved in other species, where several studies demonstrated that mycoviruses are also able to modify the production of effectors and secondary metabo-lites [12,13,65].…”
Section: Discussionmentioning
confidence: 67%
“…In C. parasitica , “biosynthesis of other secondary metabolites”, “amino acid metabolism”, “carbohydrate metabolism”, and “translation” were enriched among the DEGs after CHV1 infection, demonstrating that virus infection resulted in massive but specific changes in primary and secondary metabolism. Some of the highly induced metabolites played key roles in the growth, development and pathogenicity of fungi [ 52 ]. The complex interaction between leucine metabolism and the global regulator of mycotoxin biosynthesis, TRI6, and virulence in F. graminearum has been explored [ 53 ].…”
Section: Discussionmentioning
confidence: 99%